Do Probiotics During In-Hospital Antibiotic Treatment Prevent Colonization of Gut Microbiota With Multi-Drug-Resistant Bacteria? A Randomized Placebo-Controlled Trial Comparing Saccharomyces to a Mixture of Lactobacillus, Bifidobacterium, and Saccharomyces - Wieërs, Grégoire; Verbelen, Valérie; Van Den Driessche, Mieke; Melnik, Ekaterina; Vanheule, Greet; Marot, Jean-Christophe; Cani, Patrice D. (Frontiers in Public Health, 2021)
Objective : Most infections with AmpC β-lactamase, ESBL and carbapenemase producing bacteria, Vancomycin Resistant Enterococcus but also naturally resistant non-fermenting bacteria as Pseudomonas aeruginosa are related to a prior colonisation of the gut microbiota. The objective of the study is to investigate whether a treatment with probiotics during an antibiotic treatment could prevent colonisation of the gut microbiota with multi-drug resistant bacteria. Method : 120 patients treated with amoxicillin-clavulanate antibiotics were included in a randomised, placebo controlled, double-blinded trial comparing placebo, Saccharomyces boulardii CNCM I-745® and a probiotic mixture containing Saccharomyces boulardii, Lactobacillus acidophilus NCFM, Lactobacillus paracasei Lpc-37, Bifidobacterium lactis Bi-04 and Bifidobacterium lactis Bi-07 (Probactiol duo®). Stools were collected at the time of inclusion into the trial, at the end of the antibiotic treatment and at the end of the study treatment. These were cultured on selective antibiotic media. Results: Treatment with the probiotic mixture led to a significant decline of Pseudomonas colonisation after an antibiotic treatment from 25% to 8.3% (p= 0.041). Colonisation with AmpC producing enterobacteria was transiently increased after the antibiotic treatment (p= 0,027) and declined after the intervention (p= 0.041). No significant changes were observed in the two other groups. Up to two years after the trial, no infection with ESBL producing bacteria was observed in the probiotic mixture group. Conclusion : Specific strains of Lactobacillis and Bifidobacteria exert an influence on the colonisation of the colon microbiota with antibiotic-resistant pathogens.